1999
DOI: 10.1046/j.1525-1497.1999.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient capacity to consent to treatment

Abstract: OBJECTIVE:To compare results of a specific capacity assessment administered by the treating clinician, and a Standardized Mini-Mental Status Examination (SMMSE), with the results of expert assessments of patient capacity to consent to treatment. DESIGN:Cross-sectional study with independent comparison to expert capacity assessments. SETTING:Inpatient medical wards at an academic secondary and tertiary referral hospital. PARTICIPANTS:One hundred consecutive inpatients facing a decision about a major medical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(165 citation statements)
references
References 23 publications
5
154
0
6
Order By: Relevance
“…First, the patient has to receive adequate information about the study, with a complete disclosure of the risks and benefits from the investigator (disclosure) [3]. Second, the patient should be able to understand the implications of this research and the potential consequences of his decision to participate (decision-making capacity) [4]. Third, the patient should be able to decide freely to participate without any external pressure and to resign from the study at any time without any consequences on his care (voluntariness) [5].…”
Section: Introductionmentioning
confidence: 99%
“…First, the patient has to receive adequate information about the study, with a complete disclosure of the risks and benefits from the investigator (disclosure) [3]. Second, the patient should be able to understand the implications of this research and the potential consequences of his decision to participate (decision-making capacity) [4]. Third, the patient should be able to decide freely to participate without any external pressure and to resign from the study at any time without any consequences on his care (voluntariness) [5].…”
Section: Introductionmentioning
confidence: 99%
“…After an interval of 10 minutes, LN was unable to recall any of the target words, even with category and forced choice assistance. Structured and semi-structured interview instruments, such as the Assessment of the Capacity to Consent to Treatment (ACCT) interview [26] and Aid to Capacity Evaluation (ACE) [27] can assist clinicians in evaluating DMC.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Other well-known validated tools such as the MacArthur Competence Assessment Tool for Treatment (MacCAT-T), (9) despite its excellent inter-rater reliability and ease of use, was not included in Sessums et al's review, as it does not have a gold standard comparator. In the same systematic review, the authors found that the Mini-Mental State Examination (MMSE), which is not designed to assess incapacity, is most commonly used in clinical practice to evaluate a patient's mental capacity.…”
Section: Using Capacity Assessment Toolsmentioning
confidence: 99%